SIH: segmented intensity histogram for orientation estimation in image matching. Issue 6 (September 2016) - Peker, Murat; Karakaya, Fuat
Abstract In this paper, we propose a fast and effective new method to reduce the overhead cost of orientation estimation. The proposed method uses the summation of intensity values from segments of image patches and forms a histogram based on those values. As a result, it is faster than SIFT-like algorithms because it does not require computation of gradient orientations and magnitudes. Also, it is as fast as other intensity-based algorithms with better image matching performance. Proposed method could be easily integrated to any image matching algorithms. Test results indicate that SIFT integrated with proposed orientation estimation method produces comparable results as the original multi-angle SIFT algorithm with less execution time.